Re-Layout Lantai 1 dan Ruang Lurah Pada Gedung Kantor Kelurahan Kramatjati Jakarta Timur - Margareta Maria Sudarwani; Sally Septania; Sri Pare Eni; Grace Putri Dianty; Gabrielle Charles; Jourdan Lesilolo; Jessica Miracella Indri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2024)
ABSTRACT Comfort in the subdistrict office is an important factor in creating a productive work environment and supporting optimal public service performance. The subdistrict office is an entity that functions as a representation of the local government that is directly related to the needs of the community. Therefore, the comfort of the subdistrict office is crucial because it has the potential to improve the quality of public services, strengthen the relationship between the government and residents, and support employee welfare. Currently, the decreasing number of office employees has caused the Kramatjati Subdistrict Office to be too overloaded in accommodating activities and as a result of the office usage schedule, the Kramatjati Sucdistrict Office seems not to be optimally utilized, so it is necessary to redesign or re-design several rooms in the Kramatjati Subdistrict Office. so that it is more aesthetic and comfortable and more organized so that it can increase comfort in carrying out activities in the office. Therefore, the solution to the problem that was carried out was the Re-layout program for the 1st Floor and Subdistrict Head Room in the Kramat Jati Subdistrict Building. In this Collaboration Program, the UKI Architecture Study Program was asked for assistance from partners to provide design proposals for the Re-layout for the 1st Floor and Subdistrict Head Room. This activity involves lecturers and students of the Architecture Study Program, Faculty of Engineering, Indonesian Christian University as an effort to contribute to society in the field of architectural science. Keywords: re-layout, subdistrict head’s room, Subdistrict Office Building, Kramatjati.